O visível e o sonoro em Édipo-Rei: uma análise foucaultiana - Incerti, Fabiano (2013)
The goal of this paper is to analyze, from the interpretations made by Michel Foucault, how visual and sound are crucial for the discovery of truth (manifestation de la vérité) tragedy Oedipus the King by Sophocles. These elements are problematized, first of all, on what the French thinker understands, it is one of the central themes of the play: the plot involving Oedipus develops in terms of a legal process. In this sense, looking and listening become key elements of the outcome of the issues involving the play: the investigation and discovery of the perpetrator of a crime and the punishment of the criminal. There is no revelation of truth in the story of the hero of the Greek poet despite the different and complementary ways of seeing and listening. And second, with regards to the figure of Oedipus. For Foucault, it is the subject of power-knowledge, over knowledge and over power. And it is precisely for this Power-Knowledge in excess, for that rude awakening and denial to hear the truth that is presented before him, he falls into the trap of his own destiny. Oedipus, the subject of knowledge and power, but also the subject of looking and listening